1974
DOI: 10.1104/pp.54.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism of Rumex Leaf Tissue in the Presence of Senescence-regulating Hormones and Sucrose

Abstract: Hormones which inhibit senescence of Rumex leaf tissue in the dark include gibberellin A3, and the cytokinins 6-benzylamino purine and zeatin. These hormones inhibit respiratory metabolism in this tissue, but do not change the pattern or total amount of oxygen consumption during senescence. Abscisic acid, a senescence accelerator, correspondingly stimulates oxygen consumption. This correlation of senescence rate and respiration rate holds with regard to the hormone concentrations effective and the continued ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…We have shown previously that the rate of respiratory CO2 efflux of mature wheat leaves is correlated with the rate of prior CO2 assimilation, via carbohydrate accumulation (3), and similar correlations have been found in leaves of other species (5,14). Exogenous sugars stimulate CO2 efflux and 02 consumption in the dark in the leaves of Rumex acetosa (9) and Avena sativa (17), and similar effects have been observed with maize root tips (16).…”
supporting
confidence: 49%
“…We have shown previously that the rate of respiratory CO2 efflux of mature wheat leaves is correlated with the rate of prior CO2 assimilation, via carbohydrate accumulation (3), and similar correlations have been found in leaves of other species (5,14). Exogenous sugars stimulate CO2 efflux and 02 consumption in the dark in the leaves of Rumex acetosa (9) and Avena sativa (17), and similar effects have been observed with maize root tips (16).…”
supporting
confidence: 49%
“…Both proteolysis and Chl loss can be effectively prevented by cytokinins and, in a few cases, also by gibberellins (e.g. 4,13). The mechanism of this interference with hydrolytic reactions is under active study.…”
mentioning
confidence: 99%
“…Furthermore, isocitrate oxidation activity both in the presence and absence of ATP was enhanced by ABA. (6), and Rumex leaf discs (5). In these experiments, whole plants and tissues treated with ABA have been used.…”
Section: Resultsmentioning
confidence: 99%
“…Goldthwaite (5) observed that ABA stimulates oxygen consumption during senescence of Rumex leaf discs. Hourmant and Penot (6) reported that the rate of respiration of aerated potato tuber discs increased after a 24-h aging period with ABA in the dark.…”
mentioning
confidence: 99%